Biomimetic Restorative Dentistry: an evidence-based discussion of common myths - Alessandra REIS; Victor Pinheiro FEITOSA; Ana Cláudia CHIBINSKI; Michael Willian FAVORETO; Mario Felipe GUTIERREZ; Alessandro Dourado LOGUERCIO (University of São Paulo, 2024)
Abstract This narrative review critically examines some protocols of biomimetic restorative dentistry (BRD), which supposedly outperforms traditional adhesive techniques. This review explores the origins of BRD, introduces cognitive biases influencing the adoption of BRD protocols without evidence scrutiny, and discusses nine BRD protocols. For this, we searched randomized clinical trials and systematic reviews in the literature on the PubMed, Embase, and Cochrane Library CENTRAL databases, which lead to the following conclusions about the revised protocols: 1) The use of dyes excessively removes carious dentin; 2) Aluminum oxide air abrasion contributes to overtreatment and may pose long-term health risks to dental professionals; 3) Beveling enamel in posterior teeth is technically difficult and leads to unnecessary loss of adjacent sound enamel with no evidence of its use outperforming butt-joint preparations; 4) Deactivating matrix metalloproteinases with chlorhexidine shows no clinical evidence of improving restoration longevity. 5) "Elected" gold-standard adhesive systems perform no better than other good performing available systems; 6) Immediate dentin sealing and resin coating result in similar post-operative sensitivity and longevity of indirect fillings as delayed dentin sealing; 7) Deep margin elevation is a viable alternative to manage subgingival margins in occlusoproximal cavities; 8) The process of "decoupling" with time lacks scientific evidence to support its use; 9) Placing fiber inserts on the pulpal floor and/or axial wall to minimize stress offers no benefits over current alternatives. In conclusion, more rigorous research is needed to validate BRD protocols, focusing on important clinical outcomes that impact in the longevity of the restoration, such as fracture, debonding, post-operative sensitivity, esthetic quality, presence of caries lesions adjacent to restorations and patients' satisfaction need to be thoroughly investigated. Reliance on anecdotal evidence, clinical experience, and common sense propagates myths and undervalues the need for a critical approach in evaluating dental techniques.